Peran Otoritas Jasa Keuangan (OJK) dalam Mengawasi Maraknya Pelayanan Financial Technology (Fintech) di Indonesia - Elvira Fitriyani Pakpahan; Jessica Jessica; Corris Winar; Andriaman Andriaman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The purpose of this research is to give insights on how Fintech and the role of OJK in supervising the services of Fintech in Indonesia. The presence of Fintech in Indonesia greatly helps citizens in accessing and provide easiness in financial transactions. At the moment, Fintech provides several functions that are believed to develop rapidly and Fintech also provides services on electronic money, virtual account, aggregator, lending, crowdfunding and other online monetary transactions. Various businesses that are part of Fintech are startups and online businesses. Therefore, the government should provide legal protection in order to protect both parties, the business organizers and the possible customers. In this case, business organizers with legal Fintech development have potential that is related to consumer protection, stable financial system, economy, and payment methods. The method of the research that is used in conducting this journal is the applied law research method. This research is using normative law with the facts approach and Constitution approach. In this case, Bank Indonesia has issued the Bank Indonesia Regulation No. 18/40/PBI/2016 about the implementation of the payment transaction and the Bank Indonesia Regulation No. 19/12/PBI/2017 about the implementation of Financial Technology. Along with OJK Regulation No. 13/POJK.02/2018 about the innovation of digital money in the financial services sector as a provision that covers the supervision and stipulates financial technology (fintech) industry issued by Otoritas Jasa Keuangan (OJK). Tujuan dari penelitian ini adalah untuk memberikan pengetahuan bagaimana Fintech dan peran OJK dalam mengawasi maraknya pelayanan Fintech di Indonesia. Munculnya Fintech di Indonesia sangat membantu masyarakat untuk mengakses dan mempermudah transaksi keuangan. Saat ini, Fintech memiliki berbagai fungsi yang diyakini mampu berkembang cepat dan Fintech mampu melayani electronic money, virtual account, agregator, lending, crowdfunding dan transaksi keuangan online lainnya. Berbagai usaha yang termasuk dalam Fintech adalah bisnis startup dan bisnis online. Dengan demikian Pemerintah harus memberikan suatu bentuk perlindungan hukum baik itu dari segi penyelenggara bisnis maupun untuk masyarakat yang berperan sebagai nasabah. Dalam hal ini, Pelaksanaan bisnis yang dijalankan secara legalitas untuk pengembangan fintechnya memiliki potensi resiko yang berhubungan dengan perlindungan konsumen, stabilitas sistem keuangan dan ekonomi ,serta sistem pembayaran. Metode penelitian yang digunakan dalam penyusunan jurnal ini adalah metode hukum yuridis normatif. Dimana penelitian ini meneliti hukum secara normatif dengan menggunakan pendekatan fakta dan pendekatan Undang-Undang. Dalam Hal ini Bank Indonesia (BI) mengeluarkan Peraturan Bank Indonesia No 18/40/PBI/2016 dan Peraturan Bank Indonesia No 19/12/PBI/2017 serta Peraturan OJK No. 13/POJK.02/2018 sebagai bentu pengawasan dan pengaturan industri financial technology (fintech) yang dikeluarkan oleh Otoritas Jasa Keuangan (OJK).